Кулан (Equus hemionus Pall., 1775) и его воспроизводство - Треус, В.Д.; Лобанов, Н.В. (Вестник зоологии, 1974)
﻿
The data on 7 subspecies of Equus hemionus Pall. in nature are presented. By January 1, 1970 there were 117 Equus hemionus Pall., 88 Eq. h. onager Boddaert and 10 Eq. h. kiang Moorer at zoological gardens of the world. 5 and 6 of Equus hemionus Pall. were brought to «Askania Nova»; in 1963-1971 the progeny - 23 foals was obtained (25-in May, 3-in June). The pregnancy lasted for 340±5 days. Most females gave the first progeny at the age of 4.